Early effects of oral administration of lafutidine with mosapride compared with lafutidine alone on intragastric pH values - Koide Tomoko; Takahashi Hirokazu; Sakamoto Yasunari; Akiyama Tomoyuki; Hosono Kunihiro; Endo Hiroki; Nozaki Yuichi; Inamori Masahiko; Iida Hiroshi; Tokoro Chikako; Abe Yasunobu; Nakajima Atsushi (BMC Gastroenterology, 2009)
Abstract Background The ideal medication for treatment of acid related diseases should have a rapid onset of action to promote hemostasis and resolution of symptoms. The aim of our study was to investigate the inhibitory effects on gastric acid secretion after a single oral administrations of lafutidine, is a newly synthesized H2-receptor antagonist, with mosapride 5 mg or lafutidine alone. Methods Ten Helicobacter pylori negative male subjects participated in this randomized, two-way crossover study. Intragastric pH was monitored continuously for 4 hours after a single oral administration of lafutidine 10 mg or lafutidine 10 mg with mosapride 5 mg (the lafutidine being administrated one hour after the mosapride). Each administration was separated by a 7-day washout period. Results The average pH during the 4-hour period after administration of lafutidine 10 mg with mosapride 5 mg was higher than after lafutidine 10 mg alone (median: 5.25 versus 4.58, respectively; p = 0.0318). During the 3–4 hour study period, lafutidine 10 mg with mosapride 5 mg provided a higher pH, compared to lafutidine 10 mg alone (median: 7.28 versus 6.42; p = 0.0208). Conclusion In H. pylori negative healthy male subjects, an oral dose of lafutidine 10 mg with mosapride 5 mg more rapidly increased intragastric pH than lafutidine 10 mg alone.